Service Quality of Brady Cronin, E-SQ, and E-CRM Models in Building Loyalty Through Nagari Bank Customer Commitment in Padang City - Susriyanti; Nandan Lima Krisna; Lusiana (Universitas Pendidikan Ganesha, 2023)
This study aims to investigate the relationship between e-service quality, e-satisfaction, e-trust, and e-commitment in building customer e-loyalty. This study used a quantitative descriptive approach, with primary data collected through questionnaires distributed to respondents who were customers of Bank Nagari in Padang City. The population of this study consisted of all Bank Nagari customers in Padang City, and the sample taken was 200 respondents. The instrumentation of this study uses the Likert scale to measure respondents' perceptions of the variables studied. The collected data was analyzed using the Smart PLS (Partial Least Squares) program as a data analysis method. This analysis method includes descriptive analysis to see descriptive statistics of the variables studied, as well as inferential analysis to test the relationship between these variables, including testing the validity and reliability of tests, t-tests, path coefficients, effect measures, and hypothesis testing. The results showed that electronic service quality, electronic satisfaction, electronic trust, and electronic commitment have a significant relationship with electronic customer loyalty. Based on the results of the study, it can be concluded that the quality of electronic service, electronic satisfaction, electronic trust, and electronic commitment have an important role in building electronic customer loyalty. The implication of this research is that organizations need to pay attention to and improve these aspects in an effort to build strong e-customer loyalty.